Influence of Some Anions on the Dissolution of 1100 Aluminium in Hydrochloric Acid - Yadav, P.N.S.; Wadhwani, R. (Asian Journal of Chemistry, 2010)
An investigation has been made to find out the influence of sodium acetate, citrate, chromate, nitrate, oxalate, orthophosphate, dihydrogen orthophosphate, phosphate, perchlorate, tartrate, tetraborate, thiosulphate, tungstate and vanadate in the concentration range 1–300 ppm on the dissolution of 1100 aluminium in acidic solution containing chloride ions. It has been observed that chromate, oxalate, thiosulphate, nitrate, acetate, vanadate, tetraborate and perchlorate ions retard dissolution at all the concentrations studied. A slight increase in the corrosion rate has been noticed at lower concentrations in the presence of perchlorate. Citrate, tartrate, orthophosphate, dihydrogen orthophosphate and phosphate ions inhibit corrosion at lower concentration and accelerate at higher ones. It has been noticed that tungstate ions stimulate corrosion at all studied concentrations. Polarisation studies show that chromate ions inhibit corrosion rate by polarising cathodic reactions and tungstate ions stimulate by its depolarising actions.